The Role of Religious Leaders in the Development of Islamic Religious Education in Brekat Tegal Village - Nanang Lidwan; Maksum Maksum; Maolana Nopiansah; Faizal Roni (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
Religious figures are one of the important actors in shaping people's behavior in religion and behavior. The phenomenon that occurs in the role of religious leaders has great implications for the community in fostering Islamic religious education. The purpose of this study is to understand the role of religious leaders in Brekat Village in fostering good Islamic religious education and good religious behavior. Therefore, researchers conducted research on whether the role of religious leaders has an influence on society or not. This research is a study with a qualitative approach, which is research that produces analytical procedures that do not use statistical analysis or ways of using statistical analysis or other quantitative methods. The results of this study indicate that some of the roles of religious leaders as leaders, mobilizers, mentors, role models and educators and participate in activities that support such activities as recitation, betakziyah, visiting the sick and attending the celebration of their citizens attending the celebration of their citizens. Keywords: Religious Figures, Islamic Religious Education Development